Fiscal Sustainability: the Unpleasant European Case - Afonso, António (2010)
The sustainability of fiscal deficits has been receiving increasing attention. The issue is paramount for the newly formed euro area and this is one of the motivations of this paper. In order to assess the sustainability of budget deficits, co-integration tests between public expenditures and public revenues, allowing for structural breaks, are performed for the EU countries for the 1970-2003 period. The "unpleasant" empirical results show that with few exceptions fiscal policy may not have been sustainable. EU governments therefore could risk becoming inherently highly indebted, even if the debt-to-GDP ratios seemed to be somehow stabilising at the end of the 1990s